Health professionals as mobile content creators: Teaching medical students to develop mHealth applications. (October 2014) - Masters, Ken
Abstract Introduction: Patient access to health information and patient–provider communication is integral to medicine, and can be facilitated by mobile applications ("apps"). Traditionally, student training in mobile Health (mHealth) has focussed on health professionals as consumers of information, with negative impacts on the quality and value of medical apps. This study focuses on teaching medical students to develop their own medical apps. Methods: At Sultan Qaboos University, Oman, an app development environment, iBuildApp, was taught to medical students and used to develop their first apps. Students were surveyed on their perceptions of the project. Results: Of the 166 students, 107 (64.5%) completed the survey. There was an increase in the perceived need for such learning, apps were aimed primarily at patients, and previous programming experience was the strongest influencer of a positive experience. A majority (77.6%) wanted more sophisticated development environments in spite of their apparent struggles. Discussions: The impact of previous experience is similar to other studies; the perceived value and focus on patient apps is indicative of an awareness of patients' use of the devices not reflected in all literature. Conclusion: It is possible to teach medical students the fundamentals of app design so that they may contribute to app development in the future.